Rare Variants in NOD1 Associated with Carotid Bifurcation Intima-Media Thickness in Dominican Republic Families - Dueker, Nicole D. (PLoS One, 2016)
Cardiovascular disorders including ischemic stroke (IS) and myocardial infarction (MI) are heritable; however, few replicated loci have been identified. One strategy to identify loci influencing these complex disorders is to study subclinical phenotypes, such as carotid bifurcation intima-media thickness (bIMT). We have previously shown bIMT to be heritable and found evidence for linkage and association with common variants on chromosome 7p for bIMT. In this study, we aimed to characterize contributions of rare variants (RVs) in 7p to bIMT. To achieve this aim, we sequenced the 1 LOD unit down region on 7p in nine extended families from the Dominican Republic (DR) with strong evidence for linkage to bIMT. We then performed the family-based sequence kernel association test (famSKAT) on genes within the 7p region. Analyses were restricted to single nucleotide variants (SNVs) with population based minor allele frequency (MAF) <5%. We first analyzed all exonic RVs and then the subset of only non-synonymous RVs. There were 68 genes in our analyses. Nucleotide-binding oligomerization domain (NOD1) was the most significantly associated gene when analyzing exonic RVs (famSKAT p = 9.2x10(-4); number of SNVs = 14). We achieved suggestive replication of NOD1 in an independent sample of twelve extended families from the DR (p = 0.055). Our study provides suggestive statistical evidence for a role of rare variants in NOD1 in bIMT. Studies in mice have shown Nod1 to play a role in heart function and atherosclerosis, providing biologic plausibility for a role in bIMT thus making NOD1 an excellent bIMT candidate.